Tinjauan Sistematis Dampak Limbah Medis terhadap Kesehatan: Analisis Artikel Tahun 2016-2025 - Aisha Rizqa Aulia; Zakianis Zakianis (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Medical waste is one of the major public health concerns due to its potential direct impact on human health. One of the key factors contributing to the increased risk of disease transmission from medical waste is improper waste management, including the handling of sharp objects, infectious waste, and emissions from incineration processes that produce hazardous compounds. Studies have shown that exposure to medical waste can lead to infectious diseases such as Hepatitis B, Hepatitis C, as well as toxic effects caused by heavy metals and dioxin emissions from incinerators. This systematic review aims to examine the impact of medical waste exposure on human health based on studies published between 2016 and 2025. The research employed the Systematic Review method following the PRISMA guidelines. Articles were identified through databases including PubMed, Scopus, ScienceDirect, ProQuest, and SAGE Journals. A total of ten studies that met the inclusion criteria were analyzed in depth. The findings indicate that exposure to medical waste contributes to an increased risk of infectious diseases, Needlestick and Sharp Injuries (NSSI), respiratory disorders, and toxic effects on vital organs. Moreover, hazardous chemical compounds such as heavy metals, dioxins, furans, and volatile organic compounds (BTEX) were found to exert carcinogenic and cytotoxic effects on humans. Therefore, safe and sustainable medical waste management is essential to prevent long-term health impacts among healthcare workers, waste handlers, and communities living near healthcare facilities.